The study in cockscomb mineral composition - A. S. Deyneka; V. V. Protska; I. O. Zhuravel; O. A. Kyslychenko; V. Yu. Kuznietsova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Cockscomb (Сelosia cristata (L.) Kuntze) is grown in Ukraine mostly as a decorative plant. According to literature, it contains phenolic, terpenic, steroid, and nitrogen-containing compounds, showing a large range of biological activity.